Témoigner après des attentats : des identités collectives projectives qui oscillent entre repli local et élan national - Seoane, Annabelle (Studia Romanica Posnaniensia, 2024)
This reflection will focus on a corpus of testimonies collected in Metz a few months after the terrorist attacks on November 13, 2015 in France. We will discuss how the media narratives of these attacks build an internalized representation of a national event among speakers who live 350 km away from the site of these attacks. It emerges a balance between cohesive momentum and local withdrawal, in particular through the involvement and the emotion of citizens. We will show that the distance Lorraine/Paris and its suburbs appears in a polarizing or unifying apprehension. Through the prism of the media consulted, an articulation occurs between projective collective identities and frozen identities of the past.